Alterations in Phosphorylated CREB Expression in Different Brain Regions following Short- and Long-Term Morphine Exposure: Relationship to Food Intake. (29th August 2013) - Ren, Xiuhai; Lutfy, Kabirullah; Mangubat, Michael; Ferrini, Monica G.; Lee, Martin L.; Liu, Yanjun; Friedman, Theodore C.
Abstract : Background . Activation of the cyclic adenosine monophosphate (cAMP)/phosphorylated CREB (P-CREB) system in different brain regions has been implicated in mediating opioid tolerance and dependence, while alteration of this system in the lateral hypothalamus (LH) has been suggested to have a role in food intake and body weight. Methods . Given that opioids regulate food intake, we measured P-CREB in different brain regions in mice exposed to morphine treatments designed to induce different degrees of tolerance and dependence. Results . We found that a single morphine injection or daily morphine injections for 8 days did not influence P-CREB levels, while the escalating dose of morphine regimen raised P-CREB levels only in the ventral tegmental area (VTA). Chronic morphine pellet implantation for 7 days raised P-CREB levels in the LH, VTA, and dorsomedial nucleus of the hypothalamus (DM) but not in the nucleus accumbens and amygdala. Increased P-CREB levels in LH, VTA, and DM following 7-day treatment with morphine pellets and increased P-CREB levels in the VTA following escalating doses of morphine were associated with decreased food intake and body weight. Conclusion . The morphine regulation of P-CREB may explain some of the physiological sequelae of opioid exposure including altered food intake and body weight.